SARS-CoV-2 Infection Triggers Auto-Immune Response in ARDS - Juanes-Velasco, Pablo; Landeira-Viñuela, Alicia; García-Vaquero, Marina L.; Lecrevisse, Quentin; Herrero, Raquel; Ferruelo, Antonio; Góngora, Rafael; Corrales, Fernando; Rivas, Javier De Las; Lorente, Jose A.; Hernández, Ángela-Patricia; Fuentes, Manuel (Frontiers in Immunology, 2022)
Acute respiratory distress syndrome (ARDS) is a severe pulmonary disease, which is one of the major complications in COVID-19 patients. Dysregulation of the immune system and imbalances in cytokine release and immune cell activation are involved in SARS-CoV-2 infection. Here, the inflammatory, antigen, and auto-immune profile of patients presenting COVID-19-associated severe ARDS has been analyzed using functional proteomics approaches. Both, innate and humoral responses have been characterized through acute-phase protein network and auto-antibody signature. Severity and sepsis by SARS-CoV-2 emerged to be correlated with auto-immune profiles of patients and define their clinical progression, which could provide novel perspectives in therapeutics development and biomarkers of COVID-19 patients. Humoral response in COVID-19 patients’ profile separates with significant differences patients with or without ARDS. Furthermore, we found that this profile can be correlated with COVID-19 severity and results more common in elderly patients.